2001
DOI: 10.1080/135406000020029873
|View full text |Cite
|
Sign up to set email alerts
|

Self-Initiated Learning Activities of Experienced Public School Teachers: methods, sources, and relevant organizational influences

Abstract: The self-initiated learning activities of experienced public school teachers are examined in this study. Twenty-two experienced teachers were interviewed to develop a greater understanding of the types of self-initiated learning activities in which they engage and the organizational characteristics that in¯uence their participation in those activities. Analysis of the data showed that experienced teachers engaged in three types of self-initiated learning activities: knowledge exchanging, experimenting, and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 4 publications
3
59
0
Order By: Relevance
“…Previous studies also found that lack of time (Lohman, 2009(Lohman, , 2006, lack of proximity to colleagues' working areas (Abdul Wahab et al, 2012;Lohman, & Woolf, 2001), lack of support from others (Ellstromet al, 2008;Jurasaite-Harbison, 2009) and structural inhibitor (Ellinger, 2007;JurasaiteHarbison, 2009) were the factors that inhibited professionals' informal learning activities. The study results are also in tandem with behaviorist orientation of adult learning theory, which postulated that situations within one's immediate work environment can influence informal learning activities (Pavlov, 1927;Skinner, 1938;Watson, 1930).…”
Section: Conclusion Implications and Future Researchmentioning
confidence: 99%
“…Previous studies also found that lack of time (Lohman, 2009(Lohman, , 2006, lack of proximity to colleagues' working areas (Abdul Wahab et al, 2012;Lohman, & Woolf, 2001), lack of support from others (Ellstromet al, 2008;Jurasaite-Harbison, 2009) and structural inhibitor (Ellinger, 2007;JurasaiteHarbison, 2009) were the factors that inhibited professionals' informal learning activities. The study results are also in tandem with behaviorist orientation of adult learning theory, which postulated that situations within one's immediate work environment can influence informal learning activities (Pavlov, 1927;Skinner, 1938;Watson, 1930).…”
Section: Conclusion Implications and Future Researchmentioning
confidence: 99%
“…The term professional learning reflects the more 'agentive nature' of teacher development as described by Taylor (2015). On the basis of studies highlighting the importance of addressing teachers as active agents in educational change efforts (Hoban 2002) and studies on employees' agency (Billett 2004(Billett , 2011, teachers can be viewed as agents that self-direct their learning process (Lohman and Woolf 2001, Janssen et al 2012, Wells 2013. Self-directed learning as a concept is derived from adult learning theories that position the learner to have a sense of personal autonomy in their learning.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The combination of questions aimed to let teachers discuss such things as their concerns (cf. Hoekstra et al 2007), recent learning experiences and activities (Lohman and Woolf 2001), feelings of mastery and their aims and long-term plans (Janssen et al 2012). From these various perspectives and the follow up-questions we aimed to deduce teachers' professional learning goals (see Data analysis section).…”
Section: Instrumentmentioning
confidence: 99%
“…During the last decade, some studies have been conducted on teachers' learning activities in the workplace (e.g. Henze, 2006;Kwakman, 2003;Lohman & Woolf, 2001;Meirink et al, 2007;Van Eekelen et al, 2006;Zwart, Wubbels, Bolhuis & Bergen, 2008). Kwakman (2003) distinguishes in her study four (types of) learning activities: (1) reading (e.g.…”
Section: Learning Activities and Learning Outcomesmentioning
confidence: 99%